2007
DOI: 10.1111/j.1365-3016.2007.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood lipid profile and associated factors: baseline data of a birth cohort study

Abstract: Summary The cord blood lipid profile may be associated with lifelong changes in the metabolic functions of the individual. The aim of the present study was for the first time in Iran to assess the cord blood lipid profile of neonates, as well as some of its environmental influencing factors. The subjects were 442 (218 boys and 224 girls) normal vaginal delivery newborns. Overall, 14.4% of neonates were preterm and the rest were full‐term. In total, 9.2% (n = 35) of the full‐term newborns were small‐for‐gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
35
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 25 publications
(35 reference statements)
11
35
1
1
Order By: Relevance
“…In our findings, the mean of TC, LDL-C and TG levels were significantly higher and the mean level of HDL-C was significantly lower than the previous studies (28,31). Also the mean levels of TC, LDL-C were significantly higher and the mean levels of TG and HDL-C were significantly lower than the study in the center of Iran by Kelishadi and et al (Table 5) (22). The intake of high calorie foods during pregnancy (particularly saturated fats) could induce maternal hypercholesterolemia; which may have an effect on the lipid metabolism of the fetus (10, 12, 32).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In our findings, the mean of TC, LDL-C and TG levels were significantly higher and the mean level of HDL-C was significantly lower than the previous studies (28,31). Also the mean levels of TC, LDL-C were significantly higher and the mean levels of TG and HDL-C were significantly lower than the study in the center of Iran by Kelishadi and et al (Table 5) (22). The intake of high calorie foods during pregnancy (particularly saturated fats) could induce maternal hypercholesterolemia; which may have an effect on the lipid metabolism of the fetus (10, 12, 32).…”
Section: Discussioncontrasting
confidence: 54%
“…This is also noticeable in children (42). There are several studies which demonstrated these differences are already apparent at birth (22,31). These studies showed that TC, HDL-C, LDL-C and TG levels have been higher in female versus male neonates (43).…”
Section: Discussionmentioning
confidence: 70%
“…While maternal hyperglycemia/hyperinsulinemia contributes to increased fetal growth and the development of metabolic disorders in offspring (25), recent work suggests that maternal pregravid weight and triglyceride (TG) levels may be a better correlate of excessive fetal growth (26)(27)(28)(29). These findings imply that maternal hyperlipidemia alone could contribute to the development of metabolic disorders in offspring.…”
Section: Introductionmentioning
confidence: 83%
“…These programmed changes can later be the cause for the origin of diseases like coronary artery disease, diabetes mellitus and hypertension. The cord blood lipid profile may be associated with lifelong changes in the metabolic functions of the individual [1]. It is well documented that atherosclerosis starts in childhood and there is evidence that this association with adult levels may originate at birth, so assessment of serum lipid levels in neonates might be of importance.…”
Section: Introductionmentioning
confidence: 99%